2022
DOI: 10.5599/jese.1373
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical corrosion performance of Si-doped Al-based automotive alloy in 0.1 M NaCl solution

Abstract: The aim of this study is to investigate the electrochemical corrosion behavior of Al-Si automotive alloys with different levels of Si doping in 0.1 M NaCl solution at room temperature. The study was performed by electrochemical method, using potentiodynamic polarization and electrochemical impedance spectroscopy techniques. The condition of surfaces was characterized by both optical and scanning electron microscopy. Both the EIS and Tafel analyses revealed that the corrosion resistance was improved with the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Afterward, the solutionized samples were subjected to machining to produce 5 mm × 5 mm × 12 mm rectangular samples. They were kept at 200 °C for 240 mins to gain the peak aged condition [13]. The surfaces were polished with emery papers of 320, 600, 800, 1200, and 2000 grit sizes to get a smooth surface finish.…”
Section: Materials Preparation and Experimental Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, the solutionized samples were subjected to machining to produce 5 mm × 5 mm × 12 mm rectangular samples. They were kept at 200 °C for 240 mins to gain the peak aged condition [13]. The surfaces were polished with emery papers of 320, 600, 800, 1200, and 2000 grit sizes to get a smooth surface finish.…”
Section: Materials Preparation and Experimental Techniquementioning
confidence: 99%
“…In the potentiodynamic polarization technique, a potential difference is applied between the working and reference electrodes, and the produced current is measured, which represents the corrosion rate occurring on the exposed surface of the working electrode. The electrochemical corrosion behavior of aluminum alloys in different media is being investigated [13]. Adams et al conducted an experimental study adopting the polarization technique and microstructural characterization to understand the corrosion behavior of AA8011, AA4017, and AA1200 aluminum alloys exposed to nitric and acetic acid media and concluded that passive films that are formed in nitric acid are more stable than in acetic acid solution [14].…”
Section: Introductionmentioning
confidence: 99%
“…In case of HCl and NaCl environment, higher corrosion resistance is found in higher silicon added alloy as Si forms Mg 2 Si intermetallic phase with Mg, which is anodic to the aluminium matrix and may enhance the corrosion resistance of the alloys to some extent. The Mg 2 Si precipitations form SiO 2 and MgO [22,43,44]. However, in NaOH there is higher rate of H 2 generation on the exposed surfaces of the alloy with eutectic amount of Si, which may be responsible for the increased corrosion [39].…”
Section: Impedance Measurementmentioning
confidence: 99%
“…are added as alloying elements in the alloy matrix to upgrade various mechanical and physical properties of aluminum alloys [20]. Silicon as an alloying element improves not only strength but surface quality, corrosion resistance, hardness and other properties in the alloy [21,22]. The eutectic system of Al-Si has two solid phases, of which the eutectic composition is 12.2 ± 0.1 wt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation